The Role of Effective Communication in Harmonizing Work Relations and Increasing Employee Work Productivity - Sultan, Zulkifli (Golden Ratio of Human Resource Management, 2024)
This research was carried out to determine the extent of effective communication's role in harmonizing work relationships between leaders, subordinates, and co-workers and what the results of employee work productivity are due to the role of effective communication. This research was conducted at the Bawaslu office in the South Sulawesi Province, with a total research population of 552. The sample was determined using purposive sampling so that 104 people were spread across 24 (twenty-four) districts/cities with the criteria of employee tenure and status. technical executive officer. The research results show that effective communication influences work relationships and employee work productivity. However, it was found that work relations do not impact work productivity.